2020
DOI: 10.1097/mrm.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer and human papillomavirus infection: a recent literature review

Abstract: Aim:Prostate cancer is one of the most frequent cancers in men and it is reported that about one in nine men experience the disease in their lifetime. It has been found that in some cases, HPV can be a culprit for prostate cancer. The present meta-analysis study aims to examine whether human papillomavirus (HPV) serves as a foundation of human prostate cancer.Methods:Related studies to HPV and prostate cancer from 1990 to 2020 were sought in PubMed and Google Scholar. Earlier published expert reviews and syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…In this study, one patient in the younger subgroup was infected by HPV, but six patients in the elder subgroup were HPV infected. Elderly patients may have a weaker immune system, making them more susceptible to HPV, and further heightened the risk for PCa [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one patient in the younger subgroup was infected by HPV, but six patients in the elder subgroup were HPV infected. Elderly patients may have a weaker immune system, making them more susceptible to HPV, and further heightened the risk for PCa [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the prostate might be a target for HPV infections because of its anatomical location [7]. Even though HPV gene sequences were found in most usual, benign, and malignant prostate tissues [8,9], HPV infection possibly modulates the behavior of PCa cells via affecting apoptosis mechanisms, anoikis, anti-tumor immunity suppression, and resistance mechanisms, which results in metastasis [10]. However, the potential role of HR-HPV infection in PCa development has not yet been established [11].…”
Section: Introductionmentioning
confidence: 99%
“…HPVs can be classified into low-risk (6,18,31,33,34,35,39,45,51,52,56,58,59, 66, 68, and 70) and high-risk (6, 11, 42, 43, and 44) HPV types based on their association with cervical cancer [12]. HPV gene sequences are in most prostate tissues, including normal, benign, and malignant specimens [3,5,13,15]. In high-risk HPV types, E5, E6, and E7 proteins overlap with tumor-suppressor proteins in cells.…”
Section: Introductionmentioning
confidence: 99%